Parents' knowledge about Autism Spectrum Disorder and the impact of diagnosis on the family context (Research, Society and Development, 2026)
Objective. To evaluate the level of parental knowledge about ASD; to analyze the emotional and psychological impact of an ASD diagnosis on parents; to explore parental perceptions and expectations regarding the development and future of their children with ASD. Methodology. This study employs an evaluative, descriptive, and exploratory methodology with a qualitative approach, involving parents of children with ASD served by the Association of Parents and Friends of Autistic People (APAA) in Cajazeiras-PB. Data collection was carried out through a questionnaire administered in interviews, after the signing of the Informed Consent Form. From the responses, it was possible to synthesize and understand how parental knowledge and involvement in this process occurs. Results. Understanding of ASD is inconsistent. The most frequently cited signs that motivated the search for evaluation were delayed language development and difficulties in social interaction, reinforcing the heterogeneous nature of the disorder. The diagnostic process was described by most as long, tiring, and emotionally challenging. The main challenges identified were the emotional overload experienced by mothers and the difficulty in dealing with traits such as hyperactivity and cognitive rigidity. The impact on quality of life was felt by all interviewees. Conclusion. The understanding of caregivers regarding Autism Spectrum Disorder is heterogeneous, with some seeking further information after diagnosis, while others still demonstrate limited or misguided knowledge, highlighting the need for ongoing strategies to guide families.